Pengaruh Disiplin Dan Motivasi Kerja Terhadap Kinerja Karyawan - Said, Muhammad Syauqi; Mapparenta, Muwaffiq Nurimansyah (Jurnal Ilmiah Manajemen & Kewirausahaan, 2023)
This study aims to empirically examine the effect of Work Discipline and Work Motivation on Employee Performance. This research is descriptive quantitative research, which uses primary data. This research was conducted at PT Japfa Comfeed Indonesia, Tbk Poultry Breeding Division Makassar using a saturated sample technique involving 70 respondents. Data collection was carried out through the use of questionnaire techniques. After the data is collected, the analysis is done using the descriptive statistical analysis method. In addition, this research will also involve validity tests and data reliability tests to ensure the accuracy and reliability of the research results. The next stage will apply the multiple linear regression equation model to test the hypotheses proposed in this study. The results of this study indicate that Work Discipline has a positive and significant effect on Employee Performance, and Work Motivation has a positive and significant effect on Employee Performance.